DYNAMIC BEHAVIOR OF TWO COLLINEAR PERMEABLE CRACKS IN A PIEZOELECTRIC LAYER BONDED TO TWO HALF SPACES - 曲贵民 周振功 王彪 (Applied mathematics and mechanics, 2005)
The dynamic behavior of two collinear cracks in a piezoelectric layer bonded to two half spaces under harmonic anti-plane shear waves was investigated by means of Schmidt method. The cracks are vertically to The boundary conditions of the electrical field the interfaces of the piezoelectric layer. were assumed to be the permeable crack surface. By using the Fourier transform, the problem can be solved with the help of two pairs of triple integral equations. Numerical examples were presented to show the effect of the geometry of the interacting cracks, the piezoelectric constants of the materials and the frequency of the incident waves upon the stress intensity factors. The results show that the dynamic field will impede or enhance the propagation of the crack in a piezoelectric material at different stages of the frequency of the incident waves. It is found that the electric displacement intensity factors for the permeable crack surface conditions are much smaller than that for the impermeable crack surface conditions.